URGENSI PENGEMBANGAN KURIKULUM DALAM PENDIDIKAN SISWA SEKOLAH DASAR - Primanita Sholihah Rosmana; Sofyan Iskandar; Deti Indah Kiranti; Ismaya Febriyanti; Septy Qurrotu Aini Farradhillah; Yunita Sari (STKIP Persada Khatulistiwa Sintang, 2022)
In implementing education, the curriculum occupies a strategic position in determining the quality of educational output. In addition, in its development the curriculum must pay attention to the existing foundations such as the philosophical foundation, psychological basis, sociological basis and also the basis of science and technology. The curriculum is always changing according to changes that occur in society which are also the impact of the curriculum itself. The curriculum is not static, but dynamic and is constantly influenced by changes in the underlying factors. In developments and changes in the curriculum, it is intended to be better than the previous curriculum. In its implementation, this study uses a qualitative research type with a literature study method, where this method is used to get the main answers to problems in the urgency of the curriculum development foundation. The analysis used is descriptive analysis, which intends to explore and clarify an existing phenomenon or social reality.